An Analysıs of QRIS Usage Behavıor Usıng UTAUT Approach - Ciptowati, Liana; Setiawan, Doddy (APMBA (Asia Pacific Management and Business Application), 2024)
Quick Response Code Indonesian Standard (QRIS) is an electronic tool for transactions in Indonesia that uses a standardized national QR code. QRIS helps the growth of micro, small, and medium enterprises and facilitates domestic payment transactions. It also encourages financial inclusion. In this study, the UTAUT technique is used to describe the factors that can influence the tendency to use certain technologies. This study uses quantitative research methods, and the main data collection tool is a questionnaire. In this study, the sample consists of 110 people who work in Micro, Small, and Medium Enterprises and use the Quick Response Code Indonesian Standard (QRIS) digital transaction tool. This study was conducted using structural equation modeling (SEM) along with the partial least squares (PLS) method. The results showed that performance expectations, business expectations, social influence, and supportive conditions significantly influenced the decision or desire of MSME players to use QRIS as a digital payment tool. In terms of using QRIS, only the variables of social influence and enabling conditions affect the behavior of MSME players. However, user intentions may influence the relationship between performance expectations, effort expectations, social influence, and enabling variables that influence usage behavior.